Simulation and analysis of software defined cognitive frequency hopping multi beam satellite system - Heng-zhi LI; Chun-feng WANG (Tongxin xuebao)
Traditional multi-beam satellites cannot adapt to the changing traffic because of the fixed bandwidth and cannot adjust dynamically for the traffic load.In the future,the multi-beam broadband satellite system must have great flexibility and can be dynamically adjusted according to the change of the traffic flow.Beam hopping for multi-beam broadband satellite network system has been proposed to improve the traditional multi-beam broadband satellite network system performance,whose principle is to assign different beams to different time slots,rather than the allocation of bandwidth,so that in each time slot,the entire available bandwidth is allocated to each beam,and the time window is periodically applied to the beam selection system ,in the full band hopping mode,the band can be selected optimally in the duration of each beam to meet user transmission bandwidth and delay requirements.With the development of cognitive radio technology,cognitive beam hopping for multi-beam satellite system can further improve the efficiency of spectrum utilization,to meet the growing shortage of spectrum resources,to achieve large-capacity high-bandwidth broadband satellite network system,and to support the rising user service capacity and the transmission efficiency of user services under different load conditions.In addition,software definition technology is also used in satellite networks,which could achieve effective management of satellite resources to improve the utilization of satellite resources.In this paper,the principle of software-defined cognitive hopping multi-beam broadband satellite network system is discussed.The spectrum utilization efficiency and throughput are analyzed,which can be used as a reference for broadband satellite network system design.